2019
DOI: 10.1021/acsomega.9b01093
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Furanone-Based Radiopharmaceuticals for Diagnostic Targeting of COX-1 in Ovarian Cancer

Abstract: In vivo targeting and visualization of cyclooxygenase-1 (COX-1) using multimodal positron emission tomography/computed tomography imaging represents a unique opportunity for early detection and/or therapeutic evaluation of ovarian cancer because overexpression of COX-1 has been characterized as a pathologic hallmark of the initiation and progression of this disease. The furanone core is a common building block of many synthetic and natural products that exhibit a wide range of biological activities. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…3C). Our study demonstrated a 3-fold greater tumor accumulation with [ 11 C]PS13 than that reported for [ 18 F]FDF in a s.c. OvCa xenograft mouse model (14). We also demonstrated the potential of [ 11 C]PS13 to detect early stage OvCa in clinically relevant i.p.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…3C). Our study demonstrated a 3-fold greater tumor accumulation with [ 11 C]PS13 than that reported for [ 18 F]FDF in a s.c. OvCa xenograft mouse model (14). We also demonstrated the potential of [ 11 C]PS13 to detect early stage OvCa in clinically relevant i.p.…”
Section: Discussionmentioning
confidence: 67%
“…OVCAR-3 human OvCa cells (American Type Culture Collection) with high COX-1 expression (14) were cultured in RPMI 1640 medium supplemented with 20% fetal bovine serum (Gibco, Life Technologies), 1% penicillin/streptomycin (Sigma-Aldrich), and 0.01 mg/mL bovine insulin (Sigma-Aldrich). Cells were cultured in an atmosphere of 5% CO2 at 37°C.…”
Section: Tumor Xenograft Mouse Modelsmentioning
confidence: 99%
“…Novel compounds have been designed to target the COX-1 [12], especially in tumor cells and tissues where it is overexpressed [13][14][15][16][17]. From a chemical viewpoint, the molecules must carry at least three moieties: a mofezolac unit recognized through its carboxylic group by COX amino acid residues (Arg120, Tyr355, and Glu524) located at the entrance of the enzyme long hydrophobic channel that has the catalytic site on its top [18], a linker and a fluorochrome.…”
Section: Rationale Behind the Design Of The Novel Target Compoundsmentioning
confidence: 99%
“…The synthesis of 17a-b started with the conversion of 6-bromo-2-propyl-1H-benzo[de] isoquinoline-1,3(2H)-dione ( 14) into its N-propyl imide (15); in turn, reacting with 1,6hexanediamine or 1,4-phenylenediamine afforded 16a-b intermediates. The latter, in the presence of the coupling reagent and mofezolac, provided the two products 17a-b (Scheme 5).…”
Section: Chemistrymentioning
confidence: 99%
“…Therefore, in addition to non-selective classical non-steroidal anti-inflammatory drugs (NSAIDs: acetylsalicylic acid, ibuprofen, flurbiprofen, naproxen, indomethacin, diclofenac, mefenamic acid, piroxicam, etc. ), recently, COX-1-selective inhibitors [11,24], fluorescence imaging probes [25][26][27][28] and PET radioligands [25,26,[29][30][31][32] gem-difluorovinyl precursors [33]. Despite low molar activity, the [ 18 F]PS13 radioligand was evaluated for COX-1 PET imaging in monkeys.…”
Section: Introductionmentioning
confidence: 99%